Assesment of The Need and Availability of Agricultural Information at The Center for Agricultural Library and Literacy - Wardah Rufaidah, Vivit (Universitas Airlangga, 2023)
ABSTRACT The Center for Agricultural Library and Literacy of the Ministry of Agriculture (PUSTAKA Kementan) as a government agency plays an active role in disseminating information on agricultural technology. As a special library, one of the main users of LITERATURE information is officers and agricultural business actors. The study aims to determine the behavior patterns and information needs of agricultural technology agricultural officers and farming actors. Second, the study aims to determine the availability of information from the library's online database. This study was carried out quantitatively through online surveys and analysis of the library's online database. Respondents amounted to 894 people consisting of agricultural extension workers and farming entrepreneurs. The collected data were analyzed descriptively and presented in the form of tables and diagrams and qualitative analysis was carried out using a text mining approach. The results of the study show that the information needs of agricultural officers and farming actors are dominated by information on food crops and horticulture. In addition, agricultural officers and agricultural business actors are quite active in following developments in agricultural technology information with various media and types of agricultural technology information such as website or blog articles, social media content, infographics, books, and so on. Content material needed by agricultural officers and farming actors includes pest control and plant diseases, material on seeds and seedlings, and fertilizers. The results of the analysis show that the agricultural information needs covering the topics of pests and diseases, seeds and seedlings, fertilizers, harvest, and post-harvest, as well as agricultural mechanisms, are available quite a lot in the agricultural repository, where the most content and material is the topic of pests and diseases, followed by seeds and seedlings, fertilizer, harvest, and post-harvest as well as agricultural mechanization. Kajian Kebutuhan dan Ketersediaan Informasi Pertanian di Pusat Perpustakaan dan Literasi Pertanian ABSTRAK Pusat Perpustakaan dan Literasi Pertanian Kementerian Pertanian (PUSTAKA Kementan) sebagai salah satu instansi pemerintah berperan aktif dalam penyebarluasan informasi teknologi pertanian. Sebagai perpustakaan khusus, salah satu pengguna utama informasi PUSTAKA adalah petugas dan pelaku usaha pertanian. Kajian bertujuan untuk mengetahui pola perilaku dan kebutuhan informasi teknologi pertanian petugas pertanian dan pelaku usaha tani. Kedua, kajian bertujuan mengetahui ketersediaan informasi dari database online perpustakaan. Kajian ini dilakukan secara kuantitatif melalui survei online dan analisis database online perpustakaan. Responden berjumlah 894 orang yang terdiri atas penyuluh pertanian dan pelaku usaha tani. Data yang terkumpul dianalisis secara deskriptif dan disajikan berupa tabel dan diagram serta dilakukan analisis kualitatif dengan pendekatan text mining. Hasil kajian menunjukkan bahwa kebutuhan informasi petugas pertanian dan pelaku usaha tani didominasi oleh informasi tanaman pangan dan hortikultura. Di samping itu, petugas pertanian dan pelaku usaha tani sudah cukup aktif dalam mengikuti perkembangan informasi teknologi pertanian dengan berbagai media dan jenis informasi teknologi pertanian seperti artikel website atau blog, konten media sosial, infografis, buku, dan lain sebagainya. Materi konten yang dibutuhkan oleh petugas pertanian maupun pelaku usaha tani antara lain mengenai pengendalian hama dan penyakit tanaman, materi mengenai benih dan bibit, serta pupuk. Hasil analisis menunjukkan bahwa kebutuhan informasi pertanian yang meliputi topik hama dan penyakit, benih dan bibit, pupuk, panen dan pasca panen, serta mekanisme pertanian telah tersedia cukup banyak di repositori pertanian, dimana konten dan materi terbanyak adalah topik hama dan penyakit, kemudian diikuti oleh benih dan bibit, pupuk, panen dan pasca panen, serta mekanisasi pertanian.